Pengaruh Iklan dan Citra Merek terhadap Keputusan Pembelian Smartphone Xiaomi - Mashuri, Dian Imami; Febrima, Achmad Yoki (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research seeks to examine the impact of advertising and brand image on the purchasing decisions of Xiaomi smartphone users in Kota District, Pati Regency. The study employs multiple linear regression analysis, involving 97 respondents aged 17 and older who have either purchased or used a Xiaomi smartphone. The findings reveal that advertising significantly affects purchasing decisions, with a regression coefficient of 0.525 and a t-value of 5.503 (p < 0.05). Additionally, brand image also exerts a considerable influence, though to a lesser extent, with a regression coefficient of 0.208 and a t-value of 2.112 (p < 0.05). Together, these two variables account for around 39.4% of the variation in purchase decisions, underscoring the significance of effectively managing both advertising strategies and brand image to increase sales. The results indicate that although advertising plays a more substantial role, brand image also plays a key part in shaping consumer buying choices. This research recommends adopting a comprehensive marketing approach that also takes into account factors like product quality, pricing, and customer experience to further improve purchase outcomes.